(untitled) (GYMNASIUM, 2017)
The adaptation to the penitentiary environment leads to a modification in the personality of the imprisoned, the individual acquiring norms, customs and values that are characteristic to prison, thus becoming almost a passive spectator of the events around him, being in a constant state of waiting. Gradually, the more the person adapts to this penitentiary environment, the more his chances of social reintegration decrease, because the individual’s receptiveness to different reeducation programs decreases. Occupational therapy represents a new option for the reintegration process, allowing the inmates to adapt to their environment, and at the same time, to adapt the environment to their needs, re-acquiring the necessary skills to perform their daily activities with dignity and self-respect. The research hypotheses were as follows: presumably, the inmates encounter difficulties of adaptation to the social environment when they are released from prison; the occupational therapy can constitute a means to facilitate the inmates’ social reintegration. For this study, we selected two imprisoned subjects, from the Târgu Ocna Hospital Penitentiary. The subject M.M. used his own skills acquired during his detention, to socially reintegrate himself, and because of the occupation-based intervention plan, he succeeded in solving his occupational problems, this helping be more satisfied of himself and perform better, a fact proved by the reevaluation conducted after the implementation of the intervention plan. The failure of subject G.G. highlights the fact that his chances of social integration could have been higher if the occupational therapy intervention would have been administered through an occupation-based plan.